A Fluid-Solid Coupling Mathematical Model of Methane Driven by Water in Porous Coal. (16th September 2018) - Huang, Bingxiang; Lu, Weiyong
Abstract : The existence of the water-driven-methane effect in gassy coal has been verified by field tests and laboratory experiments. However, a water-driven-methane mathematical model that considers methane adsorption and desorption has not yet been established. Based on the water-driven-methane process, a fluid-solid coupling mathematical model of methane driven by water is established. The model's reliability is verified by the results of a water-driven-methane physical experiment and by using a solution of the COMSOL Multiphysics software. The space-time distribution regularities of the pore pressure, water-methane two-phase saturation, and pore pressure gradient in the water-driven-methane process are analysed. The results reveal the following. (1) The water-driven-methane fluid-solid coupling mathematical model for porous coal is reliable. (2) In the water-driven-methane process, there is an increasing zone and a decreasing zone of pore pressure in the coal sample. The increasing zone of pore pressure is closest to the side of the water inlet, and its area gradually decreases. The decreasing zone of pore pressure is closest to the side of the methane outlet, and its area gradually increases. Over time, the methane pressure in the increasing zone of pore pressure first increases and then decreases, and the methane pressure in the decreasing zone of pore pressure continuously decreases. The change (increase or decrease) rate of the methane pressure gradually decreases from both ends towards the middle of the coal sample. (3) The curve of the water saturation over time changes from a lower concave curve to a straight line, while the curve of the methane saturation with time changes from an upper convex curve to a straight line. The methane saturation in the decreasing zone of pore pressure is greater than that in the increasing zone of pore pressure. Over time, the water saturation of a specific point in space continuously increases while its methane saturation continuously decreases. Both of the increase rate of the water saturation and the decrease rate of the methane saturation gradually reduce over time. (4) The pore pressure gradient along the driving direction first decreases and then increases. The decreasing zone of the pore pressure gradient is located in the increasing zone of pore pressure, and the increasing zone of the pore pressure gradient is located in the decreasing zone of pore pressure. Over time, the pore pressure gradient at the side of the water inlet increases, and its increase rate decreases. The pore pressure gradient at the side of the methane outlet decreases, and its decrease rate decreases. The rate of increase in the pore pressure gradient at the side of the water inlet is greater than the rate of decrease in the pore pressure gradient at the side of the methane outlet.